Actualization of Social Welfare Through Law Number 4 of 2016 Regarding Public Housing Savings (TAPERA) - Damayanti, Ratih (Law Research Review Quarterly, 2016)
The birth of Law Number 4 of 2016 is one form of state efforts in ensuring social welfare in the form of meeting the needs of citizens for decent and affordable housing in the context of developing Indonesian people fully, self-identity, independent, and productive based on the Republic of Indonesia Constitution Indonesia in 1945. Efforts to meet the need for adequate shelter are still faced with the condition of the unavailability of long-term low-cost funds to support public housing finance. So that there is a need for a program that collects and provides long-term low-cost funds to support housing finance, the state is responsible for managing housing integration which is part of the housing finance system.